“Comparative Study of Functional Outcome of Dynamic Compression Plating and Interlocking Nailing For Fracture Shaft of Humerus in Adults” - Gupta, Dr. Inder Sain; Sheetal, Dr.; Chabra, Dr. Anurag (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: The diaphyseal fractures of humerus were traditionally treated conservatively, but the needs of the patients warranted surgical fixation of these fractures now. The two most popular methods of fixation are Plate Osteosynthesis and Intra-medullary fixation with Inter-locking Nail. In this study we tried to compare these two methods of fixation to arrive at the ideal choice of implant for these fractures. Materials & Methods: In this study we included 40 patients with diaphyseal fractures of humerus, who attended the department of Orthopedics and Traumatolog MAMC Agroha. The period of study was 1 year’s i.e, from September 2015 to September 2016. Results: Forty two percent of cases were in the age group 31-40 years. The males outnumbered the females. The most common cause was motor vehicle accidents amounting to 64%. Right side was involved in 65% of all cases. All operations were done within 4-6 days of injury. In the twenty patients of plate group, the Complications were: Infection-7.1%; delayed union-12%; movement restriction of shoulder-12%; movement restriction of elbow-7%. In the twenty patients of nail group, complications were: infection-6.7%; fracture end splintering-7.6%; delayed union-26.8%; movement restriction of elbow-7.6%; movement restriction of shoulder-14.3%; shoulder pain-48%. Maximum number of fractures (73.3% in plating group and 60% in nailing group) clinically united in 12 weeks but the results were statistically insignificant. Excellent results were obtained in 15 patients (73.3%) in locking plate group and 12 patients (60%) in locking nail group on functional assessment. Conclusion: Both locking plating and interlocking intramedullary nailing provided statistically comparable results for patients requiring surgical treatment of mid shaft humeral fractures. But a higher rate of excellent and good results and a tendency for earlier union was seen with locking plating group in our study. Keywords: Traumatolog, Osteosynthesis